Tracer Study Kinerja Lulusan Jurusan Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam UIN Sumatera Utara Berdasarkan Penilaian Stakeholder - Imsar, Imsar; Rahma, Tri Inda Fadhila (STKIP PGRI SITUBONDO, 2024)
This study aims to evaluate the quality of performance of graduates of the Islamic Economics Study Program, Faculty of Islamic Economics and Business, UIN North Sumatra, based on the level of stakeholder satisfaction as users, identify attributes that need to be improved, and provide recommendations for developing the quality of graduates. The approach is a mixed method with data collection through questionnaires, interviews, and documentation, which are then analyzed using descriptive statistics and presented as tables, graphs, and diagrams. The study results indicate that, in general, stakeholders are satisfied and give a good assessment of alumni performance. However, improvements are needed in communication skills, professionalism, leadership, and mastery of technology. Recommendations for departments include strengthening communication skills through language training with TOEFL certification and public speaking practice, leadership development, and increasing professionalism by implementing more practices relevant to the field of study and the needs of the world of work, including providing professional certifications required by companies.